2023
DOI: 10.3390/jmse11061118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Vortex-Induced Vibration of Double-Deck Truss Girder with Aerodynamic Mitigation Measures

Abstract: The long-span double-deck truss girder bridge has become a recommend structural form because of its good performance on traffic capacity. However, the vortex-induced vibration (VIV) characteristics for double-deck truss girders are more complicated and there is a lack of related research. In this research, wind tunnel tests were utilized to investigate the VIV characteristics of a large-span double-deck truss girder bridge. Meanwhile, the VIV suppression effect of the aerodynamic mitigation measures was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Several recent papers have adopted various research methods, especially the combination of experimental technology and numerical simulation. Using experiments to verify the accuracy of numerical simulation, and using numerical simulation to reveal the microscopic mechanism of experimental phenomena, has become a popular research method [9][10][11][12].…”
Section: Research Methods For Road-rail Bridgementioning
confidence: 99%
“…Several recent papers have adopted various research methods, especially the combination of experimental technology and numerical simulation. Using experiments to verify the accuracy of numerical simulation, and using numerical simulation to reveal the microscopic mechanism of experimental phenomena, has become a popular research method [9][10][11][12].…”
Section: Research Methods For Road-rail Bridgementioning
confidence: 99%
“…However, excessively small time steps would significantly reduce calculation efficiency. After conducting trial calculations, a time step of 1 × 10 −4 s was selected to meet the Coulomb number requirement [28,29].…”
Section: Solution Setting and Mesh Divisionmentioning
confidence: 99%
“…The boundary layer consisted of 12 layers with a linear growth rate of 1.2 for the section and accessory components, with the height of the first layer taken as 5 × 10 −5 mm to ensure a smooth transition of the near-wall mesh [57]. The total number of meshes was 0.22 million, which was sufficient after the trial calculation [28,29]. Furthermore, the Y-plus values of the truss girder section were all less than one, indicating that the mesh division met the requirements of the SST k-ω model [58].…”
Section: Solution Setting and Mesh Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical VIV of the bridge may be caused by the eddy current behind or above the bridge. Yao et al [31] explored the influence of aerodynamic measures on the VIV of a double-deck truss girder through wind tunnel tests and numerical simulations. The results showed that the upper chord fairing and the lower chord inverted L-shaped deflector plate played a vital role in suppressing VIV.…”
Section: Introductionmentioning
confidence: 99%